Intracellular Delivery of siRNAs Targeting AKT and ERBB2 Genes Enhances Chemosensitization of Breast Cancer Cells in a Culture and Animal Model - Tahereh Fatemian; Hamid Reza Moghimi; Ezharul Hoque Chowdhury (MDPI AG, 2019)
Pharmacotherapy as the mainstay in the management of breast cancer suffers from various drawbacks, including non-targeted biodistribution, narrow therapeutic and safety windows, and also resistance to treatment. Thus, alleviation of the constraints from the pharmacodynamic and pharmacokinetic profile of classical anti-cancer drugs could lead to improvements in efficacy and patient survival in malignancies. Moreover, modifications in the genetic pathophysiology of cancer via administration of small nucleic acids might pave the way towards higher response rates to chemotherapeutics. Inorganic pH-dependent carbonate apatite (CA) nanoparticles were utilized in this study to efficiently deliver various classes of therapeutics into cancer cells. Co-delivery of drugs and genetic materials was successfully attained through a carbonate apatite delivery device. On 4T1 cells, siRNAs against AKT and ERBB2 plus paclitaxel or docetaxel resulted in the largest increase in anti-cancer effects compared to CA/paclitaxel or CA/docetaxel. Therefore, these ingredients were selected for further in vivo investigations. Animals receiving injections of CA/paclitaxel or CA/docetaxel loaded with siRNAs against AKT and ERBB2 possessed significantly smaller tumors compared to CA/drug-treated mice. Interestingly, synergistic interactions in target protein knock down with combinations of CA/AKT/paclitaxel, CA/ERBB2/docetaxel were documented via western blotting.